Beauty and Morals in Folklore - Mačianskas, Feliksas (Problemos, 1972)
Referring to the material of Lithuanian folklore the author illustrates the attitude of people to beauty and morals. The conclusion is drawn that workers realised the dependence of moral principles and norms on the economic activity. Understanding of the reasons of social inequality and exploitation, class character of morals caused the formation of critical views or people and the formation of the idea or necessity to eliminate social reasons of need and moral humiliation.